Die Bedeutung der landschaftsökologischen Analyse für die geographisch-medizinische Forschung - Jusatz, Helmut J. (ERDKUNDE, 1958)
Based on the work of the German authority on tropical hygiene, Ernst Rodenwaldt, on the geomorphological analysis of the recurrence of infectious diseases, the object of this paper is to widen this method of geomedicine by including a landscape-ecological analysis of the area of the occurrence of a disease, and to demonstrate by means of some examples that this is an important task of research in geo-medicine. (Landscape-ecological analysis is understood as defined by C. Troll in his paper on the geographical investigation of landscape.) In doing so the environmental conditions of both the climatic and the edaphic spheres must be shown in their role as geo-factors for furthering the spread of an infectious disease. Using as example the occurrence in Middle Europe of a new disease, the Tularemia, the geographical and climatic conditions which enabled the infestation of this disease in a distinct area, the foreland of the Steigerwald in Franconia, are demonstrated. These environmental factors must be expressed by a continuous occurrence of the disease in the respective region. Besides this continuity of location concordant phenomena in other regions of the same or similar landscape character can also be shown. The landscape ecological point of view in geo-medicine will, in addition to the establishment of the cellular structure of the disease areas of different character of intensity, also contribute to the solution of the still unsolved questions of geographical pathology on a larger scale. For this the establishment by geographers of a generally valid division of the world into climatic zones and landscape belts is still needed since their knowledge is a sine qua non for an understanding of the zonal distribution of diseases. An illustration of this is given by a reference to the course of the recurrent fever epidemics in West Africa. The aim of geo-medical research lies in the elucidation of the interrelations between geographical events and disease occurrences to obtain a basis for counter measures against diseases. In this field the collaboration between geographers and medical scientists is essential.